2013
DOI: 10.1108/17590831311329322
|View full text |Cite
|
Sign up to set email alerts
|

Cricket as a vehicle for community cohesion: building bridges with British Muslims

Abstract: Purpose-The purpose of this paper is to review practices and research within the social change and community cohesion disciplines, with a view to applying them in the context of British Muslims and cricket. The paper aims to discuss the role of sport, and especially cricket, to help build community cohesion and bring about social change between British Muslims and the wider British society. Design/Methodology/Approach-This paper uses an inductive and critical approach. Findings-This paper suggests that, the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This could explain why, over recent years, it has been increasingly acknowledged that a substantial number of BSAs support the country of their ancestry, particularly when those countries are playing against England (Werbner, 1996). Furthermore, Yassim (2013) identified that supporting an ancestry nation creates a sense of community and inclusion for BSAs, as it forges a symbolic link with the subcontinent. As such, this enables the celebration of tradition, whilst creating a feeling of belonging with the nation that they, or their ancestors, migrated.…”
Section: Introductionmentioning
confidence: 99%
“…This could explain why, over recent years, it has been increasingly acknowledged that a substantial number of BSAs support the country of their ancestry, particularly when those countries are playing against England (Werbner, 1996). Furthermore, Yassim (2013) identified that supporting an ancestry nation creates a sense of community and inclusion for BSAs, as it forges a symbolic link with the subcontinent. As such, this enables the celebration of tradition, whilst creating a feeling of belonging with the nation that they, or their ancestors, migrated.…”
Section: Introductionmentioning
confidence: 99%
“…' (practitioner, 2.1, migrants integration) Finally, the link between social cohesion and potential impact on radicalisation was discussed by the participants. Although no research to-date has evidenced a direct link between social cohesion and radicalisation, Yassim (2013) argued that a cohesive society can minimise the risk of radicalisation among young people. A Home Affairs Select Committee report in the UK (2012) identified that lack of representation in the social and political processes and a sense of exclusion were major drivers of radicalisation.…”
Section: Social Cohesion -Developing a Conceptualisationmentioning
confidence: 99%
“…Participatory approaches provide a wide range of intervention tools for social marketers ranging from drama, art, music and sports to name but a few. Yassim (2013) provided a discourse on the use of sport in connecting communities in which it was argued that participatory approaches, such as sports, provides a common platform where individuals from various backgrounds can come together to explore and reconcile their differences. This is also in agreement with the concept of shared beliefs where identifying shared beliefs that different parts of the community hold about a given issue can help bring people together to address a social problem (Calderon, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%